2020
DOI: 10.3390/w12040959
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Fluid Dynamics Simulation Model of Sediment Deposition in a Storage Reservoir Subject to Water Withdrawal

Abstract: Siltation is one of the most common problems in storage projects and attached structures around the world, due to its effects on a project’s life span and operational efficiency. A three-dimensional computational fluid dynamics (CFD) model was applied to study the flow and sediment deposition in a multipurpose reservoir (Mosul Dam Reservoir, Iraq) subject to water withdrawal via a pumping station. A suitable control code was developed for the sediment simulation in intakes with multiblock option (SSIIM) model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For flows with a clear separation between one phase and another, the Volume of Fluid (VoF) model is used. This model is also relatively simple and efficient compared to eulerian or mixture [14].…”
Section: Numerical Analysis By Computational Fluid Dynamic (Cfd)mentioning
confidence: 99%
See 2 more Smart Citations
“…For flows with a clear separation between one phase and another, the Volume of Fluid (VoF) model is used. This model is also relatively simple and efficient compared to eulerian or mixture [14].…”
Section: Numerical Analysis By Computational Fluid Dynamic (Cfd)mentioning
confidence: 99%
“…Surface: At the top of the domain, the effects of wall friction are removed to represent atmospheric air, and d). Outlet: The outlet section is a pressure outlet representing the flow's "exit" [14]. Computational Fluid Dynamics (CFD) is the art of transforming fluid dynamics set equations in the form of integrals and derivatives into discrete algebraic forms, which a computer can solve to obtain the values of the flow field at a particular discrete point or time [19].…”
Section: Simulation For Approach Geometric Shape By Cfdmentioning
confidence: 99%
See 1 more Smart Citation
“…The wavelet arti cial neural network (WANN) model emerged as the most accurate predictor for suspended sediment load (SSL) (Zeyneb et al 2022). Mohammad et al (2020) demonstrated through the Sediment Simulation in Intakes with Multi-block option (SSIIM) model how sediment distribution re ects changes in bed level and water levels. Soil erosion, in uenced by sediment load and drainage areas, poses signi cant environmental and societal challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies should target the reduction of the incoming amount of sediment and can include the installation of a sediment bypass tunnel [14]. In the worst case scenario, the adaptation of the intake structure is a temporary solution to maintain the HPP in operation [15][16][17]. Ongoing modernisation efforts also allow the reduction of the environmental impact of HPP, which also includes the development of new fish protection concepts [18][19][20].…”
Section: Introductionmentioning
confidence: 99%